Social and Economic Change Through Salted Fish Management Efforts in Air Bangis Village West Pasaman Regency - Windy Agusti Prameswari; Beni Putra Hanafi; Iswadi Iswadi (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2023)
The main issue in this research is to examine the forms of social and economic changes caused by salted fish management efforts, as well as to explain the impacts arising from salted fish management in the village of Air Bangis, Sungai Beremas Subdistrict, Pasaman Barat Regency. The research method used is field research with qualitative methods. The study was conducted in the village of Air Bangis. Data collection techniques employed by the researcher include observation, interviews, documentation using a mobile phone, books, and pens. Primary and secondary data sources were used in this study. Data analysis techniques involve data reduction, presentation, drawing conclusions, and to ensure data validity, the researcher used source triangulation. Based on the researcher's findings, changes in the community around the salted fish management business in the Air Bangis area, Sungai Beremas Subdistrict, Pasaman Barat Regency, include social changes such as shifts in mindset and interaction patterns. Economic changes include increased income and changes in livelihoods. Besides affecting the location of salted fish management, this also has social and economic impacts on the community. Positive impacts include improved social relationships, job opportunities, and fulfilling livelihood needs, while negative impacts include environmental pollution and social jealousy between workers and those not employed in the salted fish management facility.